An evaluation of factors underlying suicide attempts in patients presenting at George Hospital emergency centre - Lourine Raubenheimer; Louis Jenkins (South African Family Practice, 2015)
Background: Roughly 130 patients are seen daily in the emergency centre (EC) at George Provincial Hospital (GPH), of whom one or two will have attempted suicide. GPH serves the population of Eden and Central Karoo Districts. Little is known about the circumstances surrounding these suicide attempts. We examined this pattern and formulated a protocol for managing these patients.